Committing to a romantic partner: does attractiveness matter? A dyadic approach - Gonzalez Avilés, Tita; Burriss, Robert P.; Weidmann, Rebekka; Bühler, Janina Larissa; Wünsche, Jenna; Grob, Alexander (Personality and individual differences, 2021)
Physical attractiveness is a highly valued trait in prospective romantic partners. However, it is unclear whether romantic partners' attractiveness is associated with commitment to the relationship. We report the results of a study of 565 male-female couples residing in Austria, Germany, or Switzerland. Employing dyadic analytical methods, we show that both men and women were more committed to their relationships if they perceived their partners as attractive. However, attractiveness also had a negative effect on commitment: People tended to feel less committed the more attractive their partners perceived themselves. Furthermore, although partners perceived themselves as similar in attractiveness to their partners, analyses revealed that similarity was not associated with commitment. Together, the findings demonstrate that attractiveness does matter for commitment to existing romantic relationships and emphasize the value of dyadic approaches to studying romantic relationships.